2015
DOI: 10.3390/molecules21010043
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Scorzonera Species Extracts Attenuate Cytokine Secretion via Inhibition of NF-κB Activation, Showing Anti-Inflammatory Effect in Vitro

Abstract: Scorzonera species are used in different folk medicines to combat many diseases, including the illnesses connected with inflammation. Previous experiments showed anti-inflammatory activity of Scorzonera extracts in vivo. S. latifolia, S. cana var. jacquiniana, S. tomentosa, S. mollis ssp. szowitsii, S. eriophora, S. incisa, S. cinerea, and S. parviflora extracts were, therefore, evaluated for their inhibitory activities of TNF-α and IL-1β production, and NF-κB nuclear translocation in THP-1 macrophages. The HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
0
19
1
Order By: Relevance
“…Species within the Scorzonera genus are a source of flavonoid aglycones and glycosides, phenolic acids and their derivatives, lignans, triterpenoids, sesquiterpenoids, dihydroisocoumarins, bibenzyl derivatives, as well other compounds [ 4 , 10 , 14 , 27 , 35 , 36 , 52 , 53 , 54 , 55 ].…”
Section: Phytochemical Composition Of Scorzonera Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Species within the Scorzonera genus are a source of flavonoid aglycones and glycosides, phenolic acids and their derivatives, lignans, triterpenoids, sesquiterpenoids, dihydroisocoumarins, bibenzyl derivatives, as well other compounds [ 4 , 10 , 14 , 27 , 35 , 36 , 52 , 53 , 54 , 55 ].…”
Section: Phytochemical Composition Of Scorzonera Speciesmentioning
confidence: 99%
“…It is spread mostly in central and southern parts of Europe, Eurasia, and Africa in arid areas [ 1 , 2 ]. Numerous species are endemic to Anatolia (Turkey) [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ], Mongolia [ 12 , 13 , 14 , 15 ], and China [ 16 , 17 , 18 ] The genus comprises approximately 180–190 species [ 19 ], including S. hispanica, whose roots are a valued vegetable, with the taste similar to asparagus [ 20 ], and S. tau-saghyz (a species of interest in terms of obtaining natural rubber) [ 21 ]. Several Scorzonera species are a source of feed for farming animals in arid regions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 Aerial parts of the plant have been reported to contain phenolics which were identified as quercetin-3-O-β-glucoside, hyperoside, hydrangenol-8-Oglucoside, swertisin, 7-methylisoorientin, 4,5-O-dicaffeoylquinic acid, 3,5-di-O-caffeoyl-quinic acid and chlorogenic acid. 27 In the current study, three samples of S. latifolia Fisc. & Mey.…”
Section: Introductionmentioning
confidence: 85%
“…According to the current study Scorzonera root extracts displayed hepatoprotective activities probably due to their chlorogenic acid contents. Derivatives of chlorogenic acid 3,4 and 3,5 dicaffeoylquinic acids were also reported to have protective activity in CCl 4 induced hepatotoxicity [26] which have also been isolated from some Scorzonera species previously [11,12] .…”
Section: Resultsmentioning
confidence: 99%
“…Antiinflammatory, antioxidant, and wound healing activities have also been reported [6][7][8][9] . Phytochemical analyses revealed that S. latifolia roots contained taraxasteryl myristate, taraxasteryl acetate, motiol, 3-β-hydroxy fern-8 en-7-one acetate, urs-12-en-11-one-3-acetyl, 3-β-hydroxyfern-7-en-6-one-acetate, olean-12-en-11-one-3-acetyl, fern-7-en-3-β-one, leucodin, β-sitosterol [3,5,10] , chlorogenic acid, chlorogenic acid methyl ester, 1,5-dicaffeoyl quinic acid, 3,5-dicaffeoyl quinic acid, methylester of 3,5-dicaffeoyl quinic acid, hydrangenol-8-O-β-glucoside, hydrangenol-4'-O-β-glucoside, scorzotomentosin-4'-O-β-glucoside and a new isocoumarine derivative [11] as well as scorzoveratrin 4'-O-β-glucoside, scorzoveratrin, scorzoveratrozit, 4,5-dicaffeoylquinic acid, 4,5-dicaffeoylquinic acid methyl ester and caffeic acid [12] . Scorzotomentosin, scorzotomentosin-4'-O-β-glucoside, scorzophtalide, scorzoerzincanin, hydrangenol, hydrangenol-4'-O-β-glucoside, hydramacrophyllol A and B have been isolated from S. tomentosa roots previously [13] .…”
Section: Research Papermentioning
confidence: 99%